AKAR SEJARAH KONSTRUKSI LITERAL MADZHAB SYÂFI’Î - Abdul Mukti Thabrani (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2009)
Madzhab Syâfi’î is known as moderate madzhab that connected to theliteralism of madzhab Maliki and rasionalism of madzhab Hanafi. But onthe other hand, the literalism consistency of this madzhab looks closenuance as the influence of the teacher, the founder of the madzhab,Imâm Mâlik bin Anas (d. 179 H), who has authority intellectually. Hecan build the literal scientific cycle that becomes an icon of madzhabSyâfi’î. This paper tries to describe historically the basic of all thosemadzhab as the basic reference for the beginners that want to know thismadzhab closely, and as a stimuli for the researchers that want to knowmore this construction and the pillars of scientific tradition from thispopular madzhab.